2017
DOI: 10.1177/0003319717695994
|View full text |Cite
|
Sign up to set email alerts
|

Podiatry Ankle Duplex Scan: Readily Learned and Accurate in Diabetes

Abstract: We aimed to train podiatrists to perform a focused duplex ultrasound scan (DUS) of the tibial vessels at the ankle in diabetic patients; podiatry ankle (PodAnk) duplex scan. Thirteen podiatrists underwent an intensive 3-hour long simulation training session. Participants were then assessed performing bilateral PodAnk duplex scans of 3 diabetic patients with peripheral arterial disease. Participants were assessed using the duplex ultrasound objective structured assessment of technical skills (DUOSATS) tool and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Waveform analysis was the best screening tool to exclude peripheral artery disease in our study and Normahani and colleagues [30] demonstrate that it is possible to train podiatrists to perform a focused duplex ultrasound scan of the tibial vessels at the ankle. The costs of training and the availability of ultrasound machines may be limitations.…”
Section: Discussionsupporting
confidence: 61%
“…Waveform analysis was the best screening tool to exclude peripheral artery disease in our study and Normahani and colleagues [30] demonstrate that it is possible to train podiatrists to perform a focused duplex ultrasound scan of the tibial vessels at the ankle. The costs of training and the availability of ultrasound machines may be limitations.…”
Section: Discussionsupporting
confidence: 61%
“…We have previously demonstrated that a focused DUS scan of the anterior and posterior tibial arteries at the ankle (PAD-scan; Podiatry Ankle Duplex scan; Figure S1-2, http://links.lww.com/SLA/C885) can be readily learnt and accurately performed by frontline staff. 10,11…”
mentioning
confidence: 99%
“…We have previously demonstrated that a focused DUS scan of the anterior and posterior tibial arteries at the ankle (PAD-scan; Podiatry Ankle Duplex scan; Figure S1-2, http://links.lww.com/SLA/ C885) can be readily learnt and accurately performed by frontline staff. 10,11 The primary aim of this present study is to determine the ability of the PAD-scan and other commonly performed index tests [handheld Doppler (audible and visual), ABPI, TBPI, TcPO2, and pulse palpation] to discriminate between the presence and absence of PAD in diabetes, as compared with the reference test of full lower limb arterial DUS.…”
mentioning
confidence: 99%
“…The training programme was divided into four phases over 8 weeks. The design of the programme was informed by the feedback received from our previous departmental experience of running ultrasound courses for novices [9]. All scans performed in this study utilised the Mindray M7 (Shenzhen, China) Portable Ultrasound System with a linear 6–14 kHz transducer.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…But, in order for the scan to be feasible and immediately useful in clinical practice, it must be rapidly learned, fast and accurately performed by front line healthcare workers, such as podiatrists. Our group has previously demonstrated that podiatrists with no previous ultrasound experience can be taught to perform the scan on patients with 3‐h of intensive training [9]. However, for clinical evaluation a more rigorous approach to training is required.…”
Section: Introductionmentioning
confidence: 99%